Immunotolerant indoleamine‐2, 3‐dioxygenase is increased in condyloma acuminata. (1st September 2017) - Xie, Z.; Zhang, M.; Xiong, W.; Wan, H.Y.; Zhao, X.C.; Xie, T.; Lei, H.; Lin, Z.C.; Luo, D.S.; Liang, X.L.; Chen, Y.H.
Summary: Background: The tryptophan‐depleting enzyme indoleamine‐2, 3‐dioxygenase (IDO) is critical for the regulation of immunotolerance and plays an important role in immune‐associated skin diseases. Objectives: To analyse the level of IDO in condyloma acuminata (CA) and its role in this condition. Methods: IDO expression was assessed in the skin and peripheral blood of healthy controls and patients with CA. To assess the role of skin IDO in immunity, the ability of isolated epidermal cells to metabolize tryptophan and the influence on polyclonal T‐cell mitogen (PHA)‐stimulated T‐cell proliferation were explored. Results: IDO median fluorescence intensities in peripheral blood mononuclear cells from patients with CA were similar to those from healthy controls. Immunohistochemistry showed that IDO + cells were rare in normal skin and the control skin of patients with CA, but were greatly accumulated in wart tissue. Most fluorescence signals of IDO + cells did not overlap with those of CD1a + Langerhans cells. Human papillomavirus (HPV) DNA probe in situ hybridization showed a large number of IDO + cells in the HPV − site. Keratinocytes in the skin of healthy controls and the circumcised skin of patients with CA could minimally transform tryptophan into kynurenine, but IDO‐competent epidermal cells from warts could transform tryptophan. In addition, these IDO‐competent epidermal cells could inhibit PHA‐stimulated T‐cell proliferation. The addition of an IDO inhibitor, 1‐methyl‐d ‐tryptophan, restored the inhibited T‐cell proliferation. Conclusions: Abnormally localized high IDO expression might be involved in the formation of a local immunotolerant microenvironment.